Upaya Internasionalisasi Muhammadiyah Melalui Sektor Pendidikan: Studi Kasus di Malaysia Tahun 2015-2021 - Dimas Adi Nugroho (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Muhammadiyah is a religious organization engaged in the social sphere, the role of Muhammadiyah as a civil society movement that has been widely known through its humanitarian da'wah in various fields through its business charities. At the 5-year grand event, the 47th Muhammadiyah Congress in Makassar in 2015, the Central Executive of Muhammadiyah gave the Muktamar a mandate, one of which was to take steps to internationalize. This internationalization effort is carried out through various programs through business charities in the fields of health, social and education. This study seeks to examine how the internationalization of Muhammadiyah is carried out through the education sector which will focus on the establishment of Universiti Muhammadiyah Antarbangsa Malaysia. By using qualitative research methods and data that can be analyzed, Muhammadiyah's da'wah efforts through Universiti Muhammadiyah Antarbangsa Malaysia are aimed at educating the world's life in order to build world civilization. As a non-governmental organization that operates on a religious basis, Muhammadiyah's internationalization efforts in the education sector are a step for Muhammadiyah to play an active role in the global arena in building world civilization to realize the mission of Islam rahmatan lil'alamin.